2017
DOI: 10.1080/15374416.2016.1266646
|View full text |Cite
|
Sign up to set email alerts
|

Examining Bidirectional Pathways Between Exposure to Political Violence and Adolescent Adjustment in Northern Ireland

Abstract: Objective. Research on social ecologies of political violence has been largely confined to crosssectional tests of the impact of political violence on child adjustment, limiting perspectives on more nuanced causal pathways, including tests of reciprocal relations between exposure to political violence and child adjustment. Based on a four-waves of longitudinal, this study breaks new ground in assessing bidirectional relations between exposure to political violence in the form of experience with sectarian antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…It is likely that given the legacy of the conflict in NI, young people are more reluctant to disclose personal information, and as a result the reported prevalence may be an under-estimate. Bullying, exposure to self-harm, abuse, and sexual orientation concerns were among the factors associated with self-harm, and these were also associated with exposure to the Troubles 64,66,66 .…”
Section: Young People In Schools and Collegesmentioning
confidence: 98%
“…It is likely that given the legacy of the conflict in NI, young people are more reluctant to disclose personal information, and as a result the reported prevalence may be an under-estimate. Bullying, exposure to self-harm, abuse, and sexual orientation concerns were among the factors associated with self-harm, and these were also associated with exposure to the Troubles 64,66,66 .…”
Section: Young People In Schools and Collegesmentioning
confidence: 98%
“…The relation between direct exposure to sectarian violence and more emotional insecurity about the community was stronger for girls than boys (Cummings et al, 2017a). Lastly, although exposure to sectarian violence predicted adjustment problems for both boys and girls (Cummings et al, 2010a, 2012), the reciprocal study linking adjustment problems with more sectarian violence exposure was significant only for boys (Cummings et al, 2019). As it pertains to the current study, it is possible that the effects of intergroup tension and ingroup threat in the macrosystem may differ between girls and boys.…”
Section: History Of the Projectmentioning
confidence: 99%
“…Findings showed that adolescents’ emotional insecurity about the community exacerbated the impact of family conflict on emotional insecurity about the family (Cummings et al, 2016b). Finally, investigating reciprocal relations, adjustment problems were linked with more sectarian violence exposure 1 year later for boys, and this higher exposure related to even more adjustment problems a year after that (Cummings et al, 2019).…”
Section: History Of the Projectmentioning
confidence: 99%
“…Notably, there is substantial evidence that fathers' influence child adjustment in contexts of interparental (Cummings, Merrilees, & George, 2010) and family conflict (Cummings, Koss, & Davies, 2015). However, relatively little is known about the father's role in adolescent adjustment, including the significance of father's presence on family conflict, and the potential protective influence of fathers in contexts of environmental adversity, such as low socioeconomic status (Tamis-LeMonda & McFadden, 2010) and political violence (Cummings et al, 2017). The present manuscript addresses these gaps by examining the impact of fathers on adolescent adjustment in these contexts of environmental adversity, based on six waves of longitudinal data collected on a large sample (i.e., 999) of youths in families exposed to political violence from socially deprived neighborhoods in Belfast, Northern Ireland.…”
mentioning
confidence: 99%
“…Problems for youth associated with political violence and armed conflict have been identified worldwide (Cummings et al, 2017). Moreover, links are reported between environmental adversity associated with political violence and armed conflict, family processes and psychopathology in adolescence.…”
mentioning
confidence: 99%